2002
DOI: 10.1002/humu.10027
|View full text |Cite
|
Sign up to set email alerts
|

250 CTG repeats in DMPK is a threshold for correlation of expansion size and age at onset of juvenile-adult DM1

Abstract: Myotonic dystrophy type 1 (DM1) is associated with an expansion of CTG repeats in the 3'UTR of the DMPK gene. It is accepted, as in other trinucleotide diseases, that the number of the repeats is correlated with age at onset and severity of the disease. However, assessment of genotype-phenotype correlation in DM1 is complicated with the expansion-biased somatic instability of mutant alleles over time and difficulties in precise assessment of the number of repeats by standard Southern blot hybridization. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
2
20
1
Order By: Relevance
“…Genetic analysis of this DM1 pool indicates that clinical anticipation could occur in families with transmission contraction of CTG repeats. In agreement with previous reports [25,26], we also found that the correlation between age at onset and CTG repeat size is significant only for patients with small expansions. Finally, we present evidence for the somatic mosaicism of CTG repeat sizes in a premutation carrier.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Genetic analysis of this DM1 pool indicates that clinical anticipation could occur in families with transmission contraction of CTG repeats. In agreement with previous reports [25,26], we also found that the correlation between age at onset and CTG repeat size is significant only for patients with small expansions. Finally, we present evidence for the somatic mosaicism of CTG repeat sizes in a premutation carrier.…”
Section: Discussionsupporting
confidence: 82%
“…However, our data favor the hypothesis that there exists an expansion size threshold at F250 repeats, beyond which the expansion size does not influence the onset age [25,26]. The contradictory observations could be attributed to differences in the recruitment of patient samples and the way the data were presented.…”
Section: Discussioncontrasting
confidence: 50%
“…The molecular tests diagnose patients with 100% accuracy, without overlap between normal alleles and expanded full penetrance alleles. In contrast, the clinical manifestations and their severity broadly correlate with the size of CTG repeat expansion [15][16][17], but findings vary greatly between patients.…”
Section: Discussionmentioning
confidence: 93%
“…Although large CTG repeat sizes have been correlated with early-onset DM1, there appears to be a threshold size beyond which the absolute repeat size in lymphocytes will no longer be a good indicator of age at onset in classic DM1 cases. 11,12 Hamshere et al 11 deduced that this threshold might range from 145 to 400 CTG repeats, whereas Savi c et al 12 reported a threshold value of 250 CTG repeats. Thus, repeat size may be a good predictor for age of onset in affected individuals carrying small expansions, but not in those carrying large expansions.…”
Section: Discussionmentioning
confidence: 98%
“…10 Although CTG repeat size information is potentially useful in predicting disease severity and age at onset, there appears to be no significant correlation between size and age at onset beyond a threshold repeat size, in particular for classic DM1. 11,12 Not only does DM1 exhibit phenotypic heterogeneity, it also shares some overlapping clinical features with myotonic dystrophy type 2 and other nondystrophic myotonias, which are genetically distinct disorders. 13,14 Molecular detection of the DMPK CTG repeat expansion is thus essential for definitive diagnosis of DM1.…”
mentioning
confidence: 99%